2021
DOI: 10.3389/fonc.2021.730662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative, Renal Functional, and Oncological Outcomes Between Off-Clamp and On-Clamp Robot-Assisted Partial Nephrectomy for Renal Tumors: An Updated Evidence-Based Analysis

Abstract: ObjectivesWe aimed to report the latest and largest pooled analysis and evidence update to compare the perioperative, renal functional, and oncological outcomes between off-clamp and on-clamp robot-assisted partial nephrectomy (RAPN) for renal tumors.Patients and methodsWe performed a systematic literature search using PubMed, Embase, and Web of Science up to August 2021 for studies that compared the efficacy and/or safety between off-clamp and on-clamp RAPN for renal tumors. Outcomes measured were operating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
(153 reference statements)
5
9
0
Order By: Relevance
“…The Newcastle-Ottawa Scale (NOS) and Cochrane Risk of Bias Assessment Tool (CRBAT) were utilized to evaluate the quality of the included studies [18,19]. Studies scoring 7-9 points were considered to be high quality [20]. In addition, the evidence level for every study was also assessed according to the Oxford Centre for Evidence-Based Medicine Levels of Evidence Working Group [21].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The Newcastle-Ottawa Scale (NOS) and Cochrane Risk of Bias Assessment Tool (CRBAT) were utilized to evaluate the quality of the included studies [18,19]. Studies scoring 7-9 points were considered to be high quality [20]. In addition, the evidence level for every study was also assessed according to the Oxford Centre for Evidence-Based Medicine Levels of Evidence Working Group [21].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…This procedure uses an off‐clamp method to approach the tumor from the hilum, enucleate the tumor, and seal the feeding vessel. Tumor enucleation is reportedly associated with better preservation of renal function than standard partial nephrectomy, 5 although this association is controversial 6 . The off‐clamp approach can make this technique more feasible for surgeons by taking enough time to observe layers and make the surgeons feel less stressed with no need to think about WIT, considering the difficulty and relatively long WIT needed for the hilar RAPN approach 3 .…”
Section: Figurementioning
confidence: 99%
“…Off-clamp RAPN has been described as an alternative to on-clamp RAPN to avoid the potential negative effects of warm ischaemia on renal function [9]. Systematic reviews and meta-analyses have found mostly similar perioperative outcomes between both approaches [10][11][12], but are limited by the inclusion of non-randomised studies, which contributes to selection bias.…”
Section: Introductionmentioning
confidence: 99%